1994
DOI: 10.1055/s-2008-1040746
|View full text |Cite
|
Sign up to set email alerts
|

Overwhelming Maternal Sepsis Due to a Gas-Forming Escherichia Coli Chorioamnionitis

Abstract: We report a case of a patient who developed fulminant sepsis and respiratory distress caused by a gas-forming Escherichia coli intrauterine infection following premature rupture of the membranes and fetal death. Such gas-forming infections are rare, and, when they occur, they are usually caused by Clostridium welchii. This patient was treated with antibiotics, ventilator support, and hysterectomy, and at follow-up was in good health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…120 Regardless of the primary cause of death, the fetus can act as a focus for severe secondary sepsis, including gas-forming clostridial species, which can result in severe DIC. 121,122 In one study, 3.1% of women with an IUFD developed signs of sepsis during induction of labour. 98 It has been suggested that artificial rupture of membranes may facilitate ascending infection, but no studies were found on this aspect of care.…”
Section: What Are the Recommendations For Intrapartum Antimicrobial Tmentioning
confidence: 99%
“…120 Regardless of the primary cause of death, the fetus can act as a focus for severe secondary sepsis, including gas-forming clostridial species, which can result in severe DIC. 121,122 In one study, 3.1% of women with an IUFD developed signs of sepsis during induction of labour. 98 It has been suggested that artificial rupture of membranes may facilitate ascending infection, but no studies were found on this aspect of care.…”
Section: What Are the Recommendations For Intrapartum Antimicrobial Tmentioning
confidence: 99%
“…and E coli sepsis, and continued O 2 dependence with abnormal thoracic radiographs has been recognized in foals with uroperitoneum. 10,[23][24][25][26] Although the common underlying pathophysiology of acute lung injury and acute respiratory distress syndrome is pulmonary vascular endothelial damage leading to fluid extravasation, the inciting event in foal 1 is not clear. The epsilon toxin of certain C perfringens isolates has been shown to specifically bind to the lung in mice and can induce direct vascular injury.…”
mentioning
confidence: 99%